Development of carbon paste electrode modified with cadmium ion-imprinted polymer for selective voltammetric determination of Cd2+. Issue 14 (8th December 2017) - Coelho, Malena Karla Lombello; De Oliveira, Hanna Leijoto; De Almeida, Fernanda Garcia; Borges, Keyller Bastos; Tarley, César Ricardo Teixeira; Pereira, Arnaldo César
ABSTRACT: A simple and fast voltammetric method based on a new electrode composed of carbon paste electrode/bifunctional hybrid ion imprinted polymer (CPE/IIP) was developed for the quantification of Cd 2+ in water samples. The voltammetric measurements by Differential Pulse Voltammetry were performed by using CPE containing 11.0 mg of IIP under phosphate buffer solution at concentration 0.1 mol L −1 and pH 6.5. The electrochemical method was carried out by Cd 2+ preconcentration at −1.2 V during 210 s, followed by anodic stripping. The performance of IIP towards Cd 2+ determination was evaluated by comparison to non-imprinted polymer, whose detectability of IIP was much higher (45%). The sensitivity of the sensor was found to be 0.0105 µA/µg L −1 . The limits of detection and limits of quantification were found to be 4.95 μg L −1 and 16.4 μg L −1, respectively. The developed method was successfully applied to Cd 2+ determination in mineral, tap and lake water samples, whose results are in agreement with thermospray flame furnace atomic absorption spectrometry (TS-FF-AAS) used as reference analytical technique. According to achieved results, the developed method can be used for routine analysis of quality control of water samples from different sources.